HUBUNGAN KEBISINGAN DAN BEBAN KERJA MENTAL DENGAN STRES KERJA DI PT. DURAQUIPT CEMERLANG: Relationship Between Noise and Mental Workload with Work Stress at PT. Duraquipt Cemerlang - Annur Aini; Utari, Dyah; Fithri, Nayla Kamilia; Hardy, Fathinah Ranggauni (Journal of Community Mental Health and Public Policy, 2021)
ABSTRACT Work stress is stress that is related to the work environment that can cause discomfort so that it affects the productivity of a worker. Several factors that cause work stress include individual factors, noise that exceeds the threshold value, and excessive mental workload. This study aims to determine the relationship between noise exposure, mental workload, and individual factors with work stress on workers at PT. Duraquipt Cemerlang. This study is a quantitative study using a cross-sectional study design with chi-square test analysis. The population of this study was all workers of PT. Duraquipt Cemerlang as many as 132 people. The sample of this study amounted to 106 people using the random samplng technique. This research instrument uses a sound level meter to measure noise levels, a DASS-42 questionnaire to measure work stress levels, and a NASA-TLX questionnaire to measure the mental workload. The results showed there was a relationship between education level (p=0,033) and mental workload (p=0,011) with work stress, and there was no relationship between noise (p=0,570), age (p=0,429), years of service (p=0,273), and marital status (p=0,719) with work stress. There was a relationship between mental workload and education level with work stress on PT. Duraquipt Cemerlang. The company should provide education about the prevention and control of work stress and provide consulting services for all workers.Keywords: Noise, Mental Workload, Individual Factors, Work Stress. ABSTRAKStres kerja merupakan stres yang berkaitan dengan lingkungan kerja yang dapat menimbulkan ketidaknyamanan sehingga memengaruhi produktivitas seorang pekerja. Beberapa faktor penyebab terjadinya stres kerja antara lain faktor individu, kebisingan yang melebihi NAB, dan beban kerja mental berlebih. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara paparan kebisingan, beban kerja mental, dan faktor individu dengan stres kerja pada pekerja di PT. Duraquipt Cemerlang. Metode: Penelitian ini merupakan penelitian kuantitatif menggunakan desain studi potong lintang dengan analisis uji chi-square. Populasi penelitian ini adalah seluruh pekerja PT. Duraquipt Cemerlang sebanyak 132 orang. Sampel penelitian ini berjumlah 106 orang dengan menggunakan teknik random sampling. Instrumen penelitian menggunakan sound level meter untuk mengukur tingkat kebisingan, kuesioner DASS-42 untuk mengukur tingkat stres kerja, serta kuesioner NASA-TLX untuk mengukur beban kerja mental. Hasil: Hasil uji chi-square menunjukkan adanya hubungan antara tingkat pendidikan (p=0,033) dan beban kerja mental (p=0,011) dengan stres kerja serta tidak adanya hubungan antara kebisingan (p=0,570), usia (p=0,429), masa kerja (p=0,273), dan status pernikahan (p=0,719) dengan stres kerja. Kesimpulan: Terdapat hubungan antara beban kerja mental dan tingkat pendidikan dengan stres kerja pada pekerja PT. Duraquipt Cemerlang. Bagi perusahaan diharapkan dapat melakukan sosialisasi mengenai pencegahan dan pengendalian stres kerja serta memberikan layanan konsultasi untuk seluruh pekerja.Kata Kunci: Kebisingan, Beban Kerja Mental, Faktor Individu, Stres Kerja